Solar Aureole Measurements (SAM) System Control. - George, Connor; Ware, Gene; Baker, Doran; Stair Jr., A. T.; Villanucci, Dennis (Journal of the Utah Academy of Sciences, Arts & Letters, 2014)
The Solar Aureole Measurements (SAM) system is a ground-based instrumentation system that measures the optical depth, forward scattering properties, and particle size of clouds and other atmospheric particles. These measurements use the sun's aureole as an exoatmospheric light source, as the solar disc is too bright to collect meaningful data from. To obtain accurate aureole images, it is necessary for the SAM to precisely track the solar disk across the sky. The multi-threaded SAM system control software described herein accomplishes this task, providing for automatic SAM operation system setup and user control. Visidyne, Inc., Utah State University, and the Space Dynamics Laboratory scientists and engineers are collaborating to create the SAM control system including setup, tracking, data logging, and maintenance capability.